2012
DOI: 10.1016/j.jmb.2012.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-Resolution Profiling of RNA Recombination in the Encapsidated Genome of a Eukaryotic RNA Virus by Next-Generation Sequencing

Abstract: Next-Generation Sequencing has been used in numerous investigations to characterize andquantifythe genetic diversity of a virus samplethrough the mapping of polymorphisms and measurement of mutation frequencies.Next-Generation Sequencing has also been employed to identifyrecombinationevents occurring within the genomes of higher organisms, for example, detecting alternative RNA splicing events and oncogenic chromosomal rearrangements. Here, we combine these two approaches toprofile RNA recombination within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
5
22
0
Order By: Relevance
“…As we previously reported 13 , we found numerous intra-RNA recombination events in FHV ( Table S2 ). These correlate to defective-RNAs that accumulate during viral passaging in cell culture 18 .…”
supporting
confidence: 82%
See 3 more Smart Citations
“…As we previously reported 13 , we found numerous intra-RNA recombination events in FHV ( Table S2 ). These correlate to defective-RNAs that accumulate during viral passaging in cell culture 18 .…”
supporting
confidence: 82%
“…Final cDNA library fragment sizes of 300-500 nts were selected and sequenced on an Illumina HiSeq for single-end 100 nt reads. This sequencing data (hereafter termed the ClickSeq data) was compared to our previous analyses 12; 13 that used the exact same RNA samples, but were prepared using the NEBNext RNAseq Library Prep Kit (hereafter termed the NEBNext data).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some studies have shown that recombination events should be approximately as common as mutations in the evolution of RNA viruses (32,39,40). A recent study (41) illustrated this phenomenon in the case of tobacco etch virus, a member of the same (Potyvirus) genus as PVY.…”
Section: Discussionmentioning
confidence: 99%